Armillaria mellea (Vahl. : Fr.) P. Kumm. - a non-timber forest resource in the Ñhöñho culture: promoting sustainable development and ethnomycotourism - Robles-García, Daniel; Gutierrez Santillan, Tania Vianney; Montoya-Esquivel, Adriana; Sánchez-González, Arturo (Ethnobotany Research and Applications, 2023)
Background. The indigenous and mestizo communities in Mexico have used Armillaria mellea as a non-timber forest resource, mainly as food; ecologically it is an abundant species in forests. For this reason, we establish A. mellea as a species with cultural importance and a high potential for the development of sustainable regional and ethnomycotourism projects. Methods. The field work was carried out in the Ñhöñho communities of Texquedó and Xahai, Querétaro; Mexico. Semi-structured surveys were applied to local specialists in collecting mushrooms. Species were identified at the taxonomic level. Participation-action workshops were held for the organization and development of ethnomycotourism events. Results. A total biomass of 107.11 kg of A. mellea was collected with the support of the “hongueros” (local mushroom collectors) during the rainy seasons of 2017, 2018 and 2019. A greenhouse-type solar dehydrator was designed to process the mushrooms with a minimum dehydration capacity of 30 and a maximum of 100 kg of fresh mushrooms; and value-added products were designed with edible wild mushrooms. On the other hand, tours and mushroom collections (edible and inedible) were designed with local specialists, academics and visitors; promoting and laying the foundations for the development of ethnomycotourism with an approximate economic income per year in each community of 700 to 1200 dollars. Finally, as a result of this project, the non-profit civil organization; Ethnomycology, Research and Community Development A.C. Conclusion. Mushrooms constitute the basis for the planning of regional sustainable projects, as means of revaluing traditional systems, and strengthening the local economy, as well as conservation and management under a biocultural approach. Keywords. Mycotourism, Ethnomycotourism, Value-added products, Edible wild mushrooms, Otomí, Mexico